Cover JGEET Vol 02 No 04 2017 - (J. Geoscience Eng. Environ. Technol.), JGEET (Journal of Geoscience, Engineering, Environment, and Technology, 2017)
This Volume Consists of Research Article as follow: Development of Goverment Schools Based on GIS: A Case Study of Orangi Town, Karachi. Pollen and Foraminifera Approaches to Identify Sediment Sources In The River Mouth Mahakam East Kalimantan. Structural Geology Analysis In A Disaster-Prone Of Slope Failure, Merangin Village, Kuok District, Kampar Regency, Riau Province. Sea Surface Temperature and Wind Velocity in Batam Waters Its Relation to Indian Ocean Dipole (IOD). Mapping Of Vegetation And Mangrove Distribution Level In Batam Island Using SPOT-5 Satellite Imagery. Hydro chemistry and Characteristics of Groundwater:  Case Study Water Contamination at Citarum River  Slope Stability Analysis Based on Type, Physical And Mechanical Properties Rock In Teluk Pandan District, East Kutai Regency, East Kalimantan Province. Geoelectricity Data Analysis For Identification The Aquifer Configuration In Bandorasawetan, Cilimus, Kuningan, West Java Province.